Postpartum Uterine Prolapse in a Jaffarabadi Buffalo - A Case Report - Vijyeta, H.P.; Solanki, G.B.; Chaudhary, J.K.; Parmar, K.H.; Parikh , S.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The actual cause of prolapse of uterus is not clear, but there is no doubt that it occurs during the third stage of labour within a few hours of the expulsion of the calf and at a time when some of the foetal cotyledons have separated from the maternal carbuncles (Arthur, 2001). Prolapse of the uterus is a common complication of the third stage of labour in the buffaloes (Joseph et al., 2001). In ruminants, uterine prolapse is generally a complete eversion of the gravid uterus, wherein multigravidas (dairy bovines) are more often involved than the heifers, while in the sow and the bitch eversion is generally partial and comprises of one cornua only (Arthur,2001; Jackson, 2004). The condition is predisposed by genetic as well as managemental factors and precipitated by straining, parturition and dystocia (Odegaard, 1977). The incidence of vaginal prolapse was observed to be maximum as prepartum prolapse (56.30%), followed by postpartum vaginal prolapse (12.90 %) and vaginal prolapse in non-pregnant (5.70 %) buffaloes (Pandit et al., 1982). The present paper deals with a case of postpartum complete uterine prolapse and its successful management in a Jaffarabadi buffalo.